Joel 2:17 and the Calamities of Joel 1:2-2:11 - Snoek, Doren G. (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2023)
The relationship between the calamities of Joel 1:2-2:11 remains an unsettled problem. This article contributes to discussion of the problem by attending to what the speakers in the text envision as the outcome of those calamities. Joel 2:17 is proposed as an interpretive aid, and suggestions that the wording there is ambiguous or polysemous are examined; a close analysis of syntax there and of the valence of transformative נת״נ affirms the reading of the ancient versions over against claims of inclarity or wordplay. Although the locust plague is juxtaposed and metaphorically intermingled with the invading army, the text’s speakers at this point envision the outcome of the calamities not only as agricultural disaster but also as foreign domination. While in the text the agricultural disaster is a fait accompli, the second calamity may still be averted. The possibilities of agricultural restoration and foreign domination become literary goads; the addressees are spurred to act in their own self-interest, which is entangled with the deity’s.